2012
DOI: 10.1098/rspb.2011.2545
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diurnally oscillatingpCO2on the calcification and survival of coral recruits

Abstract: Manipulative studies have demonstrated that ocean acidification (OA) is a threat to coral reefs, yet no experiments have employed diurnal variations in pCO 2 that are ecologically relevant to many shallow reefs. Two experiments were conducted to test the response of coral recruits (less than 6 days old) to diurnally oscillating pCO 2 ; one exposing recruits for 3 days to ambient (440 matm), high (663 matm) and diurnally oscillating pCO 2 on a natural phase (420 -596 matm), and another exposing recruits for 6 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
100
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 41 publications
3
100
4
Order By: Relevance
“…1) may be related to the biotic history of the corals. Putnam andedmunds (2011) andDufault et al (2012) demonstrated that corals from sites that experienced large daily fluctuations in temperature or pCO 2 were often unaffected by elevated levels of these parameters in experimental conditions. The P. furcata fragments used in this experiment were collected from a reef tract on Isla Pastores that, like most reefs inside the archipelago of Bocas del Toro, Panama, lies directly adjacent to a large mangrove habitat (<10 m distance).…”
Section: Discussionmentioning
confidence: 99%
“…1) may be related to the biotic history of the corals. Putnam andedmunds (2011) andDufault et al (2012) demonstrated that corals from sites that experienced large daily fluctuations in temperature or pCO 2 were often unaffected by elevated levels of these parameters in experimental conditions. The P. furcata fragments used in this experiment were collected from a reef tract on Isla Pastores that, like most reefs inside the archipelago of Bocas del Toro, Panama, lies directly adjacent to a large mangrove habitat (<10 m distance).…”
Section: Discussionmentioning
confidence: 99%
“…Such active control of each tank will allow for the transition of the system to one with intentional variability in each of the three controlled parameters. There is a growing need to understand the responses of organisms that live in variable environments, whether weekly, daily, or tidal timescales of variability, and how they may change in the future (Andersson and Mackenzie, 2012;Dufault et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Dufault et al [46] exposed newly settled recruits of the coral Seriatopora caliendrum to stable low pCO 2 , stable high pCO 2 , diurnally fluctuating pCO 2 on a natural phase (similar to the regime on the reef flat at Hobihu Reef, Taiwan), or diurnally fluctuating pCO 2 on a reverse phase. The recruits showed higher rates of calcification and growth under the natural phase fluctuating regime and the high pCO 2 regime as compared to the low pCO 2 regime or the reverse phase regime.…”
Section: Biological Implicationsmentioning
confidence: 99%